PENGARUH LINGKUNGAN BELAJAR DAN MINAT BELAJAR SISWA TERHADAP HASIL BELAJAR MATEMATIKA PADA SISWA KELAS X SMAN 1 KEDIRI AJARAN 2023/2024 - Nurbayani, Aluh; Amrullah; Kurniawan, Eka; Hikmah, Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The learning environment and interest in learning are two components that greatly influence students' learning outcomes. Students who have a suitable learning environment and high interest in learning tend to achieve high learning outcomes. However, students at SMAN 1 Kediri have a relatively poor quality learning environment and low interest in learning. Based on the data obtained, students' learning outcomes are low because more than 50% of them are classified below the Minimum Criteria for Mastery (KKM). Therefore, this study focuses on two variables that influence learning outcomes: the learning environment and interest in learning. This research uses a quantitative method. The population is the tenth-grade class with a total of 124 students, and a sample of 30 students is obtained using simple random sampling. Data from the tenth-grade students of SMAN 1 Kediri for the academic year 2023/2024 were collected using questionnaires and tests. By using regression analysis, the following results were obtained: 1) There is a 4.3% influence of the learning environment on students' learning outcomes; 2) There is a 14.3% influence of interest in learning on learning outcomes; 3) There is a 40.2% combined influence of the learning environment and interest in learning on learning outcomes.